2012
DOI: 10.1111/pbi.12017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetically modified red‐fleshed apples reveals effects on growth and consumer attributes

Abstract: SummaryConsumers of whole foods, such as fruits, demand consistent high quality and seek varieties with enhanced health properties, convenience or novel taste. We have raised the polyphenolic content of apple by genetic engineering of the anthocyanin pathway using the apple transcription factor MYB10. These apples have very high concentrations of foliar, flower and fruit anthocyanins, especially in the fruit peel. Independent lines were examined for impacts on tree growth, photosynthesis and fruit characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 59 publications
4
70
0
1
Order By: Relevance
“…Based on previous studies, it seems likely that variation in activity of the R2R3 MYB TFs is responsible for controlling the spatial and temporal patterning of anthocyanin production in most plant species [15], [21], [22][24]. In our work, the expression level of several MYB transcription factors involved in the regulation of flavonoids synthesis under different pH treatment conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Based on previous studies, it seems likely that variation in activity of the R2R3 MYB TFs is responsible for controlling the spatial and temporal patterning of anthocyanin production in most plant species [15], [21], [22][24]. In our work, the expression level of several MYB transcription factors involved in the regulation of flavonoids synthesis under different pH treatment conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Espley et al (2013) observed that internal browning is present in fruit of transgenic cv. Royal Gala lines modified with the MYB10 transcription factor under a constitutive promoter after 12 weeks of storage at 0.5°C, suggesting a potential postharvest issue for fruit with high anthocyanin content.…”
Section: Resultsmentioning
confidence: 97%
“…The supernatant was analysed by reversed‐phase high‐performance liquid chromatography as described by Comeskey et al (). Anthocyanin and phenolic compound identification and quantification were performed by comparison with authentic standards as per Montefiori et al () and Espley et al ().…”
Section: Methodsmentioning
confidence: 99%